The organizational culture in a private higher education institution in the perspective of different public - Just, Magela Duarte; Batistella, Claudete; Taufer, Elaine; Macke, Janaína (Contextus - Contemporary Journal of Economics and Management, 2018)
Organizations consist of different audiences that interact with each other, forming the organizational culture (OC). This investigation analyzes the OC of a private higher education institution (HEI)—IMED—from the perspective of teachers, technical-administrative personnel, and students. It is a quantitative study with descriptive statistics, which used an adapted version of the Brazilian Instrument for Evaluation of Organizational Culture (IBACO). The results suggest that the culture of the mentioned HEI manifests good interaction with the internal audience and the social forces, promoting a pleasant environment. There is consistency between the values analyzed and those of IMED, but there are differences of perception with respect to the values and practices of the HEI among audiences. The research is limited because it was performed in only one HEI. This study may help managers to draw operation strategies, strengthening the OC, and it contributes to the development of researches on OC by proposing the adaptation of the IBACO to the context of private HEIs.